Changes in The Behavior of Religious Radicalism of Young Communities in The Mataraman Region, East Java - Nur Kholis; Munardji Munardji; Nuril Mufidah; Salamah Noor Hidayati; Badrus Sholeh (AL-TAHRIR, 2021)
This study aims to describe and analyze behavioral changes in religious radicalism and the factors that influence these behavioral changes. This type of research is qualitative, using a case study approach—the place of a research area that is categorized as Mataraman culture. The primary consideration is that the character of this region adheres to the notion of integration of religion, culture, and politics, which can be called a society with a harmonious character. The facts on the ground show this community with a culture of harmony has been exposed to radical ideas, especially among teenagers. For example, there were two raids on people suspected of being exposed to radicalism in Tulungagung. Data collection techniques are in-depth interviews, observation, and documentation. The collected data were analyzed using Miles & Huberman's interactive model. The study results show that changes in behavior to become radical in religion are determined by several factors: the strength of belief, Daulah Islamiyyah as the subjective norm of the group, scriptural studies, and economic programs/activities to improve the welfare of members. These four factors strengthen the birth of the intention to turn into a radical in religion. A firm intention among youth serves to trigger the actualization of radical behavior in religion among youth. الملخصتهدف هذه الدراسة إلى وصف وتحليل التغيرات السلوكية في التطرف الديني ، والعوامل التي تؤثر على هذه التغيرات السلوكية. هذا النوع من البحث نوعي باستخدام نهج دراسة الحالة. مكان منطقة البحث المصنفة على أنها ثقافة ماتارامان. الاعتبار الرئيسي هو أن طبيعة هذه المنطقة تتمسك بفهم تكامل الدين والثقافة والسياسة ، والذي يمكن تسميته بمجتمع ذي طابع متناغم. تظهر الحقائق على الأرض أن هذا المجتمع الذي يتمتع بثقافة الانسجام قد تعرض لأفكار راديكالية ، خاصة بين المراهقين ، على سبيل المثال ، كانت هناك غارتان على الأشخاص المشتبه في تعرضهم للتطرف في تولونغاغونغ. تقنيات جمع البيانات هي المقابلات المتعمقة والملاحظة والتوثيق. تم تحليل البيانات التي تم جمعها باستخدام النموذج التفاعلي Miles & Hubermans. تظهر نتائج الدراسة أن التغيرات في السلوك ليصبح متطرفًا في الدين تتحدد بعدة عوامل هي ؛ قوة الإيمان ، الدولة الإسلامية كقاعدة ذاتية للجماعة ، والدراسات الكتابية ، والبرامج / الأنشطة الاقتصادية لتحسين رفاهية الأعضاء. هذه العوامل الأربعة تعزز ولادة نية التحول إلى راديكالية في الدين. تعمل النية القوية لدى الشباب على تفعيل السلوك الراديكالي في الدين بين الشباب. AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis perubahan perilaku radikalisme beragama, dan faktor-faktor yang mempengaruhi perubahan perilaku tersebut. Jenis penelitian ini adalah kualitatif dengan menggunakan pendekatan studi kasus. Tempat penelitian wilayah yang masuk kategori budaya Mataraman. Pertimbangan utamanya adalah karakter wilayah ini menganut paham integrasi agama, budaya, dan politik dapat disebut sebagai masyarakat berkarakter harmoni. Fakta dilapangan menunjukkan komunitas masyarakat yang berbudaya harmoni  ini telah terpapar paham radikal terutama kalangan remaja, misalnya dua kali terjadi penggerebekan orang yang diduga terpapar paham radikal di Tulungagung. Teknik pengumpulan datanya adalah Interview mendalam, observasi, dan dokumentasi. Data-data yang terkumpul dianalisis menggunakan model interaktif Miles & Hubermans. Hasil penelitian menujukkan bahwa perubahan perilaku menjadi radikal dalam beragama ditentukan oleh beberapa faktor, yaitu; kekuatan keyakinan, Daulah Islamiyyah sebagai norma subyektif kelompok, kajian-kajian yang bersifat skriptural, dan program/kegiatan ekonomi untuk meningkatkan kesejahteraan anggota. Keempat faktor ini menguatkan lahirnya niat untuk berubah menjadi radikal dalam beragama. Niat yang kuat pada kalangan pemuda berfungsi memicu aktualisasi perilaku radikal dalam beragama di kalangan pemuda.